The Role of Self Esteem and Creativity on Tiktok Usage Patterns Among Adolescents at Iskandar Muda Private High School - Jannah, Taifatul; Rahmatillah, Hilma; Fauzan; Nurjannah, Siti (Business Finance Analyst Co., 2025)
The focus of this study is to examine the role of self-esteem and creativity in TikTok usage patterns among adolescents at SMA Swasta Iskandar Muda. The sampling method used was purposive sampling, involving 130 students aged 14 to 18 years. Data were collected using three scales: the TikTok Usage Pattern Scale, the Self- Esteem Scale, and the Creativity Scale. The data analysis technique used multiple regression analysis. The results showed that (1) self-esteem significantly influenced TikTok usage patterns, with an F-value of 5.929 and p < .05, contributing 4.4% to the variance in usage patterns; (2) creativity also significantly influenced TikTok usage patterns, with an F-value of 19.637 and p < .05, contributing 13.3%; and (3) both self- esteem and creativity together significantly influenced TikTok usage patterns, with an F-value of 30.055 and p < .05, accounting for 32.1% of the variance.